1999
DOI: 10.1128/jcm.37.3.706-708.1999
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility Patterns of Aeromonas jandaei , A. schubertii , A. trota , and A. veronii Biotype veronii

Abstract: Fifty-six isolates of four Aeromonas species, which have been documented as causative agents of human infections or isolated from human clinical specimens, were subjected to antimicrobial susceptibility testing using a MicroScan WalkAway conventional (overnight incubation) gram-negative panel. The four species tested and the number of isolates of each were as follows: Aeromonas jandaei, 17; A. schubertii, 12; A. trota, 15; and A. veronii biotype veronii, 12. All isolates ofA. trota were susceptible to all anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
18
1
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 19 publications
12
18
1
2
Order By: Relevance
“…However, it is not clear if clavulanic acid shows intrinsic activity against Aeromonas, or if it inhibits the ac- Table 2 Primers designed and PCR conditions for the detection of virulence genes tivity of some of the chromosome-mediated L-lactamases. The resistance to cephalosporins shown in our study agrees with that reported for the species A. jandaei, A. schubertii, A. trota and A. veronii bt veronii [30] and also with that previously reported for A. popo¤i [3,29].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…However, it is not clear if clavulanic acid shows intrinsic activity against Aeromonas, or if it inhibits the ac- Table 2 Primers designed and PCR conditions for the detection of virulence genes tivity of some of the chromosome-mediated L-lactamases. The resistance to cephalosporins shown in our study agrees with that reported for the species A. jandaei, A. schubertii, A. trota and A. veronii bt veronii [30] and also with that previously reported for A. popo¤i [3,29].…”
Section: Resultssupporting
confidence: 92%
“…In this study, we have tested all available strains against a total of 26 antibiotics, 10 of which have never been tested against this species (piperacillin^tazobactam, cefalotin, ceftibuten, merope- nem, fosfomycin, pipemidic acid, colistin, ampicillin^sulbactam, amoxycillin^clavulanic acid and trimethoprimŝ ulfamethoxazole). As expected, all A. popo¤i strains were resistant to ampicillin, a characteristic trait for most of the species of the genus [30]. By contrast, all the strains were susceptible to piperacillin, piperacillin^tazobactam, cefalotin, cefuroxime, ceftibuten, cefotaxime, ceftazidime, aztreonam, imipenem, meropenem, gentamicin, amikacin, tobramycin, fosfomycin, pipemidic acid, cipro-£oxacin, nor£oxacin, colistin and trimethoprim^sulfame-thoxazole.…”
Section: Resultssupporting
confidence: 70%
“…And all of these tested isolates were collected from human clinical specimens. Eight antimicrobial agents were adopted both in this study and three previous reports (Kampeer, Christmann, Swings & Huys ; Overman & Janda ; Vila et al . ) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…). Antibiotic therapy is one of the most frequently used and effective methods for Aeromonas ‐mediated infections (Overman & Janda ; Vila, Marco, Soler, Chacon & Figueras ). However, there is paucity of systematic knowledge on the prevalence and antibiotic susceptibility of turtle‐source Aeromonas isolates.…”
mentioning
confidence: 99%
“…As in the present study, there are differences on antibiotic resistance according to isolated sources of Aeromonas spp. (Overman & Janda ; Aravena‐Roman et al . ).…”
Section: Discussionmentioning
confidence: 99%